ANALISIS ANALISIS ASUHAN KEPERAWATAN PADA LANSIA HIPERKOLESTEROMIA DENGAN PENERAPAN INTERVENSI GUAVA JUICE DI KELURAHAN PANGERAN BANJARMASIN UTARA: ANALISIS ASUHAN KEPERAWATAN PADA LANSIA HIPERKOLESTEROMIA DENGAN PENERAPAN INTERVENSI GUAVA JUICE DI KELURAHAN PANGERAN BANJARMASIN UTARA - Ica wati (UrbanGreen, 2022)
Antioxidants with large enough amounts can lower blood cholesterol levels where antioxidants are rich in vitamin C and can help lower cholesterol levels. A fruit with a high concentration of vitamin C, namely the guava fruit (Psidium guajava) has 183.5 mg of vitamin C per 100 grams. In addition, flavonoids and pectins are also found in the red guava. The purpose of this study was to ascertain the impact of guava juice to reduce cholesterol levels. This research method is by measuring/ assessing total cholesterol levels before (Pre-test) and after action (Post - test). The results of the study found that the cholesterol level before being given guava juice was 238 mg / dl and after 14 days Mrs. S's cholesterol level dropped to 202 mg/ dl. So after 14 days of action on Mrs.S, there was a change between the pre and post intervention of guava juice. Keywords: Antioxidants, Total Cholesterol Levels, Guava Juice